(untitled) (Literary Voice, 2024)
Mother Forest: The Unfinished Story of C.K Janu (2003) is an autobiography of C.K Janu, a tribal rights activist from Kerala. The paper examines how Janu narrates the essence of the tribal culture and its shared sense of mutuality with the environment. Describing the enriched experiences of the tribal society, achieved through ecological practices, Janu focuses on the fact that the tribal society maintains an inherent relationship with the forest. The indigenous philosophy of life and its impact on the sustenance of forest terrains, is highlighted in the narrative. The paper also examines the politics of power while analyzing Janu’s role as an activist for tribal land rights. The insensitivity of the system towards tribal culture and tribal land rights is critiqued against the backdrop of contemporary and contentious socio-political scenario.